Role of portocaval shunts in development of complications after liver transplantation - D. L. Tsoy; M. I. Prudkov; O. G. Orlov; E. N. Bessonova; I. G. Leshchenko; L. V. Kardopoltsev; A. N. Ageev; S. I. Solodushkin (Трансплантология (Москва))
Rationale. Portal blood flow is a key component in the viability of the liver transplant.Portocaval shunts formed on the background of the liver cirrhosis before transplantation can cause portal vein steal syndrome, with subsequent development of ischemic necrosis of the graft.To date, the tactics of treating patients with portal vein steal syndrome during liver transplantation has not been sufficiently developed.This paper presents a literature review and our own experience on this important, but little-studied issue.Purpose. The purpose of this research is to study the role of portocaval shunts in the development of complications after liver transplantation, based on a retrospective analysis of clinical cases.Conclusions. In liver transplantation, portocaval shunts can cause the development of portal vein steal syndrome with subsequent development of liver failure. For the diagnosis of portal vein steal syndrome, it is important to use the data obtained at all stages of liver transplantation. Surgical correction of portal vein steal syndrome can be performed during liver transplantation and in the early postoperative period.